Mathematical and computer model for helical and conical coil spring design - Gan, Hwa Cheng (2009)
In this study, a mechanical spring design programme is developed for helical and conical spring selection. The purpose of developing this spring design programme is to analyse spring requirements with the knowledge of spring geometry and operating conditions. It is also capable of analysing helical spring and conical spring solution operating under various loads and physical boundary conditions. By inputting the desired spring design data, it computes the static and fatigue strengths of the spring. This programme is written in Fortran programming language.